2017
DOI: 10.1088/1361-648x/aa80d0
|View full text |Cite
|
Sign up to set email alerts
|

Compressed H3S: inter-sublattice Coulomb coupling in a high-TCsuperconductor

Abstract: Upon thermal annealing at or above room temperature (RT) and at high hydrostatic pressure P ~ 155 GPa, sulfur trihydride HS exhibits a measured maximum superconducting transition temperature T ~ 200 K. Various theoretical frameworks incorporating strong electron-phonon coupling and Coulomb repulsion have reproduced this record-level T. Of particular relevance is that experimentally observed H-D isotopic correlations among T , P, and annealed order indicate an H-D isotope effect exponent α limited to values  ⩽ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(53 citation statements)
references
References 39 publications
1
52
0
Order By: Relevance
“…We assumed that electron effective mass is * = 3.0 • [58]. Maximal and minimal Tc/TF values are in red bold.From other hand, Hirsch and Marsiglio[53], Souza and Marsiglio[54], Harshman and Fiory[55],Kaplan and Imry…”
mentioning
confidence: 99%
“…We assumed that electron effective mass is * = 3.0 • [58]. Maximal and minimal Tc/TF values are in red bold.From other hand, Hirsch and Marsiglio[53], Souza and Marsiglio[54], Harshman and Fiory[55],Kaplan and Imry…”
mentioning
confidence: 99%
“…The high-T C nature of TBG devices is further supported circumstantially given that the two requisite physically separate charge reservoirs, denoted as types I and II in [49] as comprising the interaction structure of the model, are present in the form of the two individual graphene sheets which are separated by mean distance ζ. Because they are essentially identical, the graphene layers must each function as both reservoir types, with pairing carriers and mediating charges coexisting in each layer, much like as was found for the two interlaced sublattices forming the Im3 ത m structural phase of H 3 S [50]. The coexistence of superconducting and non-superconducting pockets in TBG devices as surmised in [22,28], together with strong interlayer electron-hole correlations [48], is consistent with the two reservoir types required.…”
Section: Interlayer Coulomb Pairing Modelmentioning
confidence: 91%
“…Such a mechanism was introduced for determining the optimal transition temperature T C0 of high-T C cuprates and other superconductors in [49], with further developments most recently reported in [50]. Pairing in this model is ascribed to Coulomb interactions between charges in adjacent reservoirs separated by a distance ζ via the exchange of virtual photons, with T C0 scaling with the root of the participating charge density 1/ℓ multiplied by the potential energy e 2 /ζ (where e is the electron charge).…”
Section: Introductionmentioning
confidence: 99%
“…Semenok et al [44] reported the discovery of a high-temperature superconducting phase of ThH 9 at P=170 GPa which exhibits P6 3 /mmc crystallographic symmetry and superconducting transition temperature of T c =146 K. They also performed first principles calculations and deduced the effective mass in this superconductor: As we mentioned in our previous papers [12,13,46,47], first principles calculations [39,48,49] always provide α-values near 5, which is the very strong-coupling limit for s-wave symmetry (also note that other superconducting gap symmetries have weak-coupling limits of α∼5 [50][51][52]). Despite the orthodox view, several new, alternative, approaches were developed to explain NRT superconductivity in compressed hydrides: Hirsch and Marsiglio [53], Souza and Marsiglio [54], Harshman and Fiory [55], as well as Kaplan and Imry [56]. For instance, Kaplan and Imry [56] showed that in the case of highly compressed H 3 S their model gives an α within the weak-coupling BCS limit:…”
Section: Thh 9 (P=170 Gpa) In Uemura Plotmentioning
confidence: 99%